“Józek, what are you doing?” The Massacre of Jews Committed by the AK in the Village of Kosowice - Mazurek, Jerzy (Zagłada Żydów. Studia i Materiały, 2013)
In the spring of 1943, in the village of Kosowice (Opatów county), in the house of Józef Machula, 5 members of the AK (Home Army) murdered 5 Jews (personal details unknown), including a woman and a child. In 1956 the case was taken to the Provincial Court of Kielce (Radom Branch). The accused were punished as a consequence